The Ecoremed protocol for an integrated agronomic approach to characterization and remediation of contaminated soils - Fagnano, Massimo; Fiorentino (Guest editors), Nunzio (Italian Journal of Agronomy, 2018)
Definition of a site as contaminated: Problems related to agricultural soils Massimo Fagnano.......... pp. 1-5 Geography of soil contamination for characterization and precision remediation of potentially contaminated sites Giuliano Langella, Antonietta Agrillo, Angelo Basile, Roberto De Mascellis, Piero Manna, Pierpaolo Moretti, Florindo Antonio Mileti, Fabio Terribile, Simona Vingiani.......... pp. 6-15 Assessing the bioavailability of potentially toxic elements in soil: A proposed approach Claudia Rocco, Diana Agrelli, Maria Tafuro, Antonio Giandonato Caporale, Paola Adamo.......... pp. 16-22 Use of the native vascular flora for risk assessment and management of an industrial contaminated soil Donato Visconti, Nunzio Fiorentino, Adriano Stinca, Ida Di Mola, Massimo Fagnano.......... pp. 23-33 Assisted phytoremediation for restoring soil fertility in contaminated and degraded land Nunzio Fiorentino, Mauro Mori, Vincenzo Cenvinzo, Luigi Giuseppe Duri, Laura Gioia, Donato Visconti, Massimo Fagnano.......... pp. 34-44 Bioassays for evaluation of sanitary risks from food crops cultivated in potentially contaminated sites Luigi Giuseppe Duri, Nunzio Fiorentino, Eugenio Cozzolino, Lucia Ottaiano, Diana Agrelli Massimo Fagnano.......... pp. 45-52 Responses of bacterial community structure and diversity to soil eco-friendly bioremediation treatments of two multi-contaminated fields Valeria Ventorino, Vincenza Faraco, Ida Romano, Olimpia Pepe.......... pp. 53-58 Monitoring and modelling the role of phytoremediation to mitigate non-point source cadmium pollution and groundwater contamination at field scale Mario Palladino, Paolo Nasta, Alessandra Capolupo, Nunzio Romano.......... pp. 59-68